2021
DOI: 10.1111/hae.14457
|View full text |Cite
|
Sign up to set email alerts
|

Dental habits and oral health in children and adolescents with bleeding disorders: A single‐institution cross‐sectional study

Abstract: Introduction Oral health is an important component of care at haemophilia treatment centres (HTCs). Correlations between oral health and inflammation suggest that proper oral health may improve joint health. Aim To evaluate the dental habits, needs, and oral health status of paediatric patients with bleeding disorders, and identify predicters of poor oral health. Methods From May 2016 to October 2017, consecutive paediatric HTC patients completed a 14‐question survey and were examined by dental professionals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…By collating and critically analysing existing research, we strive to provide a comprehensive overview of the current state of knowledge regarding this crucial subject. The meticulous examination of the available literature has revealed that there have been numerous studies assessing different oral health components in individuals with bleeding disorders [4][5][6][7] ; however, a comprehensive pooled estimate of the different oral health conditions has not been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…By collating and critically analysing existing research, we strive to provide a comprehensive overview of the current state of knowledge regarding this crucial subject. The meticulous examination of the available literature has revealed that there have been numerous studies assessing different oral health components in individuals with bleeding disorders [4][5][6][7] ; however, a comprehensive pooled estimate of the different oral health conditions has not been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Oral and dental health is a difficult thing to pay attention to for the community, especially among children [3]. This will later lead to the development of disease due to a minimal of attention to hygiene and oral and dental health [4].…”
Section: Introductionmentioning
confidence: 99%
“…Inherited bleeding disorders, notably haemophilia A and B, von Willebrand disease, other coagulation factors deficiencies, and platelet disorders, affect many people globally. [1][2][3] Severe and moderate haemophilia (factor VIII or IX activity < 1% or 1-5% of normal, respectively) are associated with spontaneous joint and muscle bleedings. 4,5 Spontaneous bleedings are more rarely encountered in mild haemophilia (factor activity: 6-40% of normal) and other inherited bleeding disorders, but bleeding can occur following trauma or surgical or dental intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Inherited bleeding disorders, notably haemophilia A and B, von Willebrand disease, other coagulation factors deficiencies, and platelet disorders, affect many people globally 1–3 . Severe and moderate haemophilia (factor VIII or IX activity < 1% or 1–5% of normal, respectively) are associated with spontaneous joint and muscle bleedings 4,5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation